An identity-based personal location system with protected privacy in IOT - Chunye Hu; Jie Zhang; Qiaoyan Wen (2011 4th IEEE International Conference on Broadband Network and Multimedia Technology, 2011)
The internet of things (IOT) has the same security requirements as traditional network, but according to the characteristics of its own, the internet of things also has some specific security features. Among these features, the flexibility of the network requires nodes to apply corresponding measures when scene changes. For example, in emergency situations (e.g. an accident occurs, and a doctor is needed), the location of the user is available, while under normal circumstances, the user's location information is confidential. This paper is in the background of the above scene to present an identity based system for personal location in emergency situations. The proposed system consists of registration subsystem, user authentication subsystem, policy subsystem and client subsystem. The system confirms the identity of the user through the user authentication subsystem and gets the level of the emergency through the policy subsystem. Then it can make sure that user's location information can be accessed only by some authorized user, and only when necessary. The proposed system strengthens the protection of the user's privacy while providing the location of the user, and prevents the disclosure of the users' information.